Healthy lifestyles in the perspective of homo eligens - Stępniak, Piotr (Journal of Medical Science, 2018)
The article is devoted to lifestyles in the context of health. According to vision of A. Siciński — lifestyle is a culturally conditioned way of meeting needs, habits and norms. They regulate the value systems adopted by an individual or group. Lifestyle is formed by the interaction of widely understood living conditions and individual patterns of behavior. Behaviors in turn are determined by personal characteristics and sociocultural factors. Lifestyle and health behaviors are shaped throughout a person's life, but its foundations are formed in childhood and adolescence. The author of the article considers that a key category in the analysis of pro or anti-healthy lifestyle is the free choice of man. A man can decide how he wants to live and also in what health he wants to live. His choices determine the way of life. The theoretical basis for discussing in this article the above-mentioned issue will be Siciński's concept of so-called homo eligens which is little known, but worthy of dissemination. It is the most important part of his theory of lifestyles.
Keywords: life style; health; freedom of choice; patient; humanistic paradigm